Implementasi Kebijakan Program Makan Bergizi Gratis dalam Mewujudkan Pemenuhan Gizi di Kabupaten Barito Utara - Muhammad Rafiqhi Alfaqih; Sitna Hajar Malawat; Rizky Subhan (Student Research Journal, 2026)
This study aims to analyze the implementation of the MBG policy in fulfilling nutritional needs in North Barito Regency and to identify the obstacles encountered. A qualitative descriptive approach was employed, with MAN Barito Utara and SMAN 4 Muara Teweh as research sites. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Edward III's policy implementation model encompassing four indicators: communication, resources, implementor disposition, and bureaucratic structure. The findings reveal that MBG implementation at both schools has generally been running well but not yet optimally. Communication was structured and food production quality was ensured through certified kitchens. All implementors demonstrated high commitment and enthusiasm, serving as the primary strength of the program. Key obstacles were identified in the resource dimension absence of dedicated nutrition personnel, inadequate distribution space, and minimal nutrition education for students and in the bureaucratic structure dimension, including SOPs not tailored to each school's specific characteristics, informal task divisions lacking official decrees, and the absence of systematic staff substitution mechanisms. The study recommends dedicated budget allocation for distribution facilities, issuance of official task division decrees, SOP refinement, and development of nutrition education modules integrated into teaching and learning activities.